The Effect of Innovation in Premium Roti Canai Products on Consumer Buying Interest at Al-Fatih Bakery Samarinda - Ginting, Cindia; Rahman W, Iqbal Fithratur (Jurnal Indonesia Sosial Sains, 2025)
Competition in the culinary industry is becoming increasingly fierce, necessitating product innovation to enhance competitiveness and attract consumer purchasing interest. This study aims to analyze the effect of Roti Canai product innovation on consumer purchase interest at Al-Fatih Samarinda Bakery. The research employs a quantitative method with a survey approach. The sample consists of 145 respondents who are customers of Al-Fatih Bakery, obtained using the total sampling technique. Data collection was conducted through an online questionnaire containing questions related to product innovation and consumer purchase interest. The data were analyzed using simple regression to examine the relationship between the product innovation variable (X) and consumer purchase interest (Y). The results indicate that product innovation significantly influences consumer purchase interest, with the regression equation . The coefficient of determination (R Square) value of 0.844 shows that product innovation explains 84.4% of the variability in consumer purchase interest. The simple regression test yields a t-value of 27.842 with a significance value of 0.000 (<0.05), indicating a positive and significant relationship between product innovation and purchase interest. These findings confirm that the higher the level of innovation in the Roti Canai product, the greater the consumer purchase interest in the product. Roti Canai product innovation significantly contributes to increasing consumer purchase interest at Al-Fatih Bakery Samarinda. Therefore, innovation strategies focusing on novelty, uniqueness, material quality, and added value should be continuously developed to maintain competitiveness and attract consumer attention in the premium culinary industry.